Pengaruh Kepercayaan, Kenyamanan dan Kualitas Layanan terhadap Kepuasan dalam Layanan BYOND by BSI (Studi Pada Pelaku UMKM Kota Banda Aceh) - Yulindawati; Eka Octavian Pranata; Raisa Amini , Raisa Amini (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
The purpose of this study is to test the hypotheses and provide empirical evidence on the influence of Trust, Convenience, and Service Quality on Customer Satisfaction in the BYOND by BSI service. This research utilizes primary data collected through questionnaires distributed to MSME (Micro, Small, and Medium Enterprises) actors who are aware of and use the BYOND by BSI service. The sampling method employed in this study is purposive sampling, with a total of 100 MSME respondents. The analytical method used to test the hypotheses is multiple linear regression analysis using SPSS version 22. The results indicate that Trust and Service Quality have a positive effect on satisfaction with the BYOND by BSI service, whereas Convenience does not have a significant positive effect.